ANALISIS PERTUMBUHAN TANAMAN GANDUM PADA BEBERAPA KERAPATAN TANAMAN DAN IMBANGAN PUPUK NITROGEN ANORGANIK DAN NITROGEN KOMPOS - Yosefina Mangera (Universitas Musamus, Merauke, Papua, 2013)
Objective of the experiment to evaluate wheat growth of some plant density and the proportionof inorganic nitrogen and compost nitrogen.The research was conducted in the Sirapu Village, Semangga District, Merauke Regency using Randomized Complete Block Design with 3 blocks as replication. The first factor was plant density of three level, i.e., 25 cm x 10 cm, 25 cm x 15 cm, 25 cm x 20 cm.The second factor was proportion of inorganic nitrogen and compost nitrogen consists of six levels, i.e., compost 0% + urea 0%, 0% compost + 100% urea, 25% compost +75% urea, 50% compost + 50% urea, 75% compost + 25% urea, 100%compost + 0%.The experiment results showed that there was interaction between plant density and the proportion of inorganic nitrogen and compost nitrogen for plant dry weigh and crop growth rate parameters.Plant density in 25 cm x 15 cm and proportion of inorganic nitrogen and compost nitrogen in 25% compost +75% urea showed the best effect in plant dry weight and crop growth rate at 42 to 63 DAP.